Comprehensive analysis of LILR family genes expression and tumour‐infiltrating immune cells in early‐stage pancreatic ductal adenocarcinoma. Issue 2 (7th February 2023) - Gao, Qiang; Mo, Shutian; Han, Chuangye; Liao, Xiwen; Yang, Chengkun; Wang, Xiangkun; Liang, Tianyi; He, Yongfei; Chen, Zijun; Zhu, Guangzhi; Su, Hao; Ye, Xinping; et al.
Abstract: Leucocyte immunoglobulin‐like receptors (LILRs) are closely related to tumourigenesis, but their clinical value in early‐stage pancreatic ductal adenocarcinoma (PDAC) after pancreaticoduodenectomy remains unknown. Kaplan–Meier and Cox proportional hazards regression models is used to investigate the association between LILR expression and prognosis in tumour biopsies and peripheral blood mononuclear cells. Risk score was calculated for each patient based on the prognostic model. DAVID, STRING, GeneMANIA, and GSEA were used to conduct pathway and functional analyses. The CIBERSORT algorithm is used to analyse tumour‐infiltrating immune cells. Survival analysis showed that high levels of LILRA4 ( p = 0.006) and LILRB4 ( p = 0.04) were significantly associated with better overall survival. High levels of LILRA2 ( p = 0.008) and LILRB4 ( p = 0.038) were significantly associated with better relapse‐free survival. JAK‐STAT signalling pathway, regulation of T cell activation, regulation of the immune effector process, and tumour necrosis factor superfamily cytokine production were involved in molecular mechanisms that affected poor prognoses in the high‐risk group in GSEA. CIBERSORT demonstrated that the high‐risk group had significantly higher infiltrating fraction of memory‐activated CD4 T cells and activated NK cells and lower fraction of resting dendritic cells and neutrophils. LILRB4 plays crucial roles in affecting the clinical outcomes of early‐stage PDAC. Abstract : LILRB4 play crucial roles in affecting the clinical outcomes of early‐stage PDAC through JAK‐STAT signalling pathway, immune‐related signalling pathways, and tumour‐infiltrating immune cells.